Facing the War: Exploring the Dilemm as of Heroes in Chinese Movies (The Macau Ricci Institute Journal, 2023)
For over 30 years I have had different opportunities to involve people from different walks of life in Asia and in Europe in workshops on Confucian ethics with a focus on the “hero,” defined by the Cambridge Dictionary as “the main character or the main male character in a book or film, who is usually good”. This type of a hero thus sticks to his or her values of respect, loyalty, compassion, and wisdom in the middle of adversities and challenges. Within the Chinese tradition of “hero” however we may not always be assured of a “Hollywood Happy Ending” as heroes do face the tragedy of war and deadly conflicts; nevertheless, the key highlight for a more systematic narrative analysis of the different dramas of heroes is to recognise in their struggles with a host of obstacles and moral dilemmas, while always facing death and destruction, a unique opportunity to reconnect to one’s own better self.